2014
DOI: 10.1039/c3fo60292c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heme iron enriched peptide on iron deficiency anemia in rats

Abstract: The present study aims to investigate whether a daily intake of heme iron enriched peptide obtained from bovine hemoglobin is effective in alleviating iron deficiency anemia (IDA). Wistar rats were randomly divided into six groups: a control group, an anemic group not treated, and anemic groups treated with FeSO4 or with the heme iron enriched peptide at low, moderate or high doses. The rats in the anemic groups were fed on a low-iron diet to establish the iron deficiency anemia model. After the model had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 55 publications
1
32
0
3
Order By: Relevance
“…The result indicated that IDA would adversely affect the growth of rats. It has been reported that the IDA rats lose their appetite [21]. From Table 3, it can be seen obviously that the food intake of the anemic rats was significantly lower than that of control rats (p < 0.05).…”
Section: Resultsmentioning
confidence: 71%
“…The result indicated that IDA would adversely affect the growth of rats. It has been reported that the IDA rats lose their appetite [21]. From Table 3, it can be seen obviously that the food intake of the anemic rats was significantly lower than that of control rats (p < 0.05).…”
Section: Resultsmentioning
confidence: 71%
“…Peptide–iron complexes can be absorbed in the form of soluble chelates as a whole and maintain it in the ferrous form in digestive condition. Ferrous irons could be effectively released across the apical membrane of the intestinal epithelium, thus chelates enhance the iron bioavailability . In summary, a significantly higher or equal hematological value for the middle dose DPs‐Fe group was observed during repletion, as compared with the FeSO 4 group, which could provide evidence that DPs‐Fe was more effective in overcoming IDA than FeSO 4 .…”
Section: Resultsmentioning
confidence: 78%
“…The process of dietary iron absorption in the duodenum are as follows: (i) the reduction of ferric iron to ferrous iron form occurs possibly by duodenal cytochrome b (Dcytb) on the apical surface of enterocytes; (ii) ferrous iron is further transported via the divalent metal transporter 1 (DMT1) into intestinal epithelial cells; (iii) once ferrous iron enters into the cell, one is interchanged with ferritin and remains in a dynamic equilibrium, the other is transferred across the basolateral membrane into the blood circulation by ferroportin 1 (FPN1); (iv) ferrous iron is then oxidized to the ferric form by hephaestin which has ferrous oxidase activity before entering the circulation by binding to the transferrin . Many iron supplements have been developed and investigated to solve this urgent problem . Iron can be supplied from inorganic iron salts, organic acid iron salts, amino acid‐iron chelates, peptide‐iron chelates.…”
Section: Introductionmentioning
confidence: 99%
“…The organ coefficient was calculated by the following formula: 21,22 Organ coefficient ¼ organ weight=rat body weight  100: A gross pathology examination was performed by visual inspection during the necropsy.…”
Section: Preparation Of Iron-enriched Yeast No Ym1504 and Cell Iron mentioning
confidence: 99%